2017
DOI: 10.1113/jp273324
|View full text |Cite
|
Sign up to set email alerts
|

Fetal adaptations in insulin secretion result from high catecholamines during placental insufficiency

Abstract: Placental insufficiency and intrauterine growth restriction (IUGR) of the fetus affects approximately 8% of all pregnancies and is associated with short- and long-term disturbances in metabolism. In pregnant sheep, experimental models with a small, defective placenta that restricts delivery of nutrients and oxygen to the fetus result in IUGR. Low blood oxygen concentrations increase fetal plasma catecholamine concentrations, which lower fetal insulin concentrations. All of these observations in sheep models wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 74 publications
0
42
1
Order By: Relevance
“…; Aljunaidy et al . ; Limesand & Rozance, ). Less is known about the consequences of postnatal undernutrition and growth retardation during the later stages of cardiac maturation, and if deficiencies incurred during this time are recoverable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Aljunaidy et al . ; Limesand & Rozance, ). Less is known about the consequences of postnatal undernutrition and growth retardation during the later stages of cardiac maturation, and if deficiencies incurred during this time are recoverable.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies in animal models have focused on the long-term cardiovascular effects of IUGR (reviewed in Kuo et al 2017). In utero, however, factors in addition to nutrient supply are likely to contribute to the outcomes, such as hypoxia, high catecholamine levels or other stress hormones, and adverse changes to maternal and feto-placental physiology (Morrison et al 2007;Bjarnegard et al 2013;Cohen et al 2016;Aljunaidy et al 2017;Limesand & Rozance, 2017). Less is known about the consequences of postnatal undernutrition and growth retardation during the later stages of cardiac maturation, and if deficiencies incurred during this time are recoverable.…”
Section: Discussionmentioning
confidence: 99%
“…; Danielson et al . ; Limesand & Rozance, ). We found that when placental insufficiency was produced by maternal hyperthermia in sheep, the resulting fetal hypercatecholaminaemia inhibited insulin secretion and independently slowed growth (Leos et al .…”
Section: Introductionmentioning
confidence: 98%
“…; Boehmer et al. ; Limesand and Rozance ). For example, fetuses from pregnancies complicated by placental insufficiency and severe intrauterine growth restriction (IUGR) are characterized by lower circulating IGF‐1 and lower β ‐cell mass (Van Assche et al.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies show important effects of IGF-1 on b-cell mass and insulin production, the physiological endocrine regulation of fetal islet development and b-cell mass are largely unexplored. Understanding this regulation is important because common complications of pregnancy result in abnormal b-cell mass and islet development with implications for fetal insulin concentrations and the regulation of fetal growth (Green et al 2010;Boehmer et al 2017;Limesand and Rozance 2017). For example, fetuses from pregnancies complicated by placental insufficiency and severe intrauterine growth restriction (IUGR) are characterized by lower circulating IGF-1 and lower b-cell mass (Van Assche et al 1977;Ostlund et al 1997).…”
Section: Introductionmentioning
confidence: 99%